Berakhlak as a New Foundation of Basic Values for the State Civil Apparatus - Suryana, Ohan; Briando, Bobby (KnE Social Sciences, 2022)
This article aimed to explore the new foundation of basic values for the state civil apparatus (ASN). For a long time, every government, both at the central and regional levels, had its own values and slogans in accordance with the spirit and uniqueness of the organization. The core values of ASN, ’Berakhlak’, was recently launched, which focuses on the principles of being service-oriented, accountable, competent, harmonious, loyal, adaptive and collaborative. Employer branding of ASN as ’Proud to Serve the Nation’ was also implemented. It was hoped that doing so would lead to all ASN, both at the central and regional levels, to have the same base values. This research involved a qualitative literature review. The results provided a new perspective on encouraging the creation of a dynamic bureaucracy with clear, effective, efficient and fast governance in making decisions through the implementation of the core values of ’Berakhlak’ and the employer branding of ’Proud to Serve the Nation’. This can be used to spur momentum to accelerate the transformation of the apparatus throughout Indonesia. Thus, the performance of the bureaucracy will be more dexterous and innovative in providing services to the community Keywords: core values, employer branding, state civil apparatus